Identifikasi Bakteri pada Nutrient Agar Plate di Laboratorium Mikrobiologi Universitas Muhammadiyah Palangkaraya: Identification of Bacteria on Nutrient Agar Plate at the Universitas Muhammadiyah Palangkaraya’s Microbiology Laboratory - Windya Nazmatur Rahmah; Fera Sartika; Yuda Ednisa Sri Maduren (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
A laboratory is a place or room carrying out research, learning, and experiment activities equipped with various equipment and materials supporting the work. This study aims to identify bacteria on nutrient agar plates at the Universitas Muhammadiyah Palangkaraya’s Microbiology Laboratory. This study uses observational research with a non-probability sampling technique with a cross-sectional research design. Bacterial samples were taken at several points using nutrient agar plates in the microbiology laboratory room. The results showed that when cultured on Nutrient Agar media in 12 glasses of petri, the results obtained were 100% bacterial growth. Bacteria identified using the gram staining method received 41.7% gram-negative Streptococcus bacteria, 41.7% gram-negative Staphylococcus, and 16.7% gram-positive Staphylococcus.